REVIEW OF NASA FIBROMYXOMA: Aggressive Behaviour? (Case Report) - Indharty, Rr. Suzy (BALI MEDICAL JOURNAL, 2015)
Background: Myxomas are rare benign tumors arising from mesenchymal tissues throughout the body. These tumors are usually seen in the atrium of the heart and the jawbone. Involvement of the skull base with intracranial extension is extremely rare, and only a few cases of primary intracranial myxomas have been described in the literature. This article presents a rare case of primary myxoma of the nasal bone. Methods: The patient underwent a skull base surgery with a pre-diagnosis of possible fibromyxomas. The tumor pathology revealed a diagnosis of myxoma with bone and meningeal involvement. Despite the debulking surgery, the tumor showed a local recurrence in five month. A second debulking surgery in piece meal was required. In the article, the etiology, histological and radiological findings as well as treatment options of this rare entity were briefly discussed under the highlights of the relevant literature. Such a localization and intracranial extension of myxomas is extremely unusual in clinical practice; the diagnosis therefore requires a high degree of suspicion and detailed histopathological examination. The differential diagnosis frequently includes chondrosarcomas, chordoma, metastatic tumors of the skull, hemangiopericytoma, meningioma and other neoplasms of the dura and skull base in this location.